Behavioural and experimental economics - Durlauf, Steven N.; Blume, Lawrence (New York : Palgrave Macmillan, 2010)
"Following the recent publication of the award winning and much acclaimed The New Palgrave Dictionary of Economics, second edition which brings together Nobel Prize winners and the brightest young scholars to survey the discipline, we are pleased to announce The New Palgrave Economics Collection. Due to demand from the economics community these books address key subject areas within the field. Each title is comprised of specially selected articles from the Dictionary and covers a fundamental theme within the discipline. All of the articles have been specifically chosen by the editors of the Dictionary, Steven N.Durlauf and Lawrence E.Blume and are written by leading practitioners in the field. The Collections provide the reader with easy to access information on complex and important subject areas, and allow individual scholars and students to have their own personal reference copy"--Provided by publisher.
All articles first published in The new Palgrave dictionary of economics, 2nd ed. in eight volumes, 2008 exception of Experimental methods in economics which first published in The new Palgrave: a dictionary of economics, in four volumes, 1987.
Includes bibliographical references and index.
Keywords: Economics -- Psychological aspects; Experimental economics